2020
DOI: 10.1155/2020/2391439
|View full text |Cite
|
Sign up to set email alerts
|

Cyclocarya paliurus Polysaccharide Inhibits Glioma Cell U251 Proliferation, Migration, and Invasion and Promotes Apoptosis via the GSK3β/β-Catenin Signaling Pathway

Abstract: Objective. To investigate the effects of Cyclocarya paliurus polysaccharide (CPP) on the proliferation, migration, invasion, and apoptosis of human glioma U251 cells and further explore the underlying mechanism. Methods. U251 cells were cultured in vitro and treated with various concentrations (25, 50, 75, 100, 125, and 150 μmol/L) of CPP for 24, 48, and 72 h. Cell counting kit-8 was used to detect the activity of cell proliferation. Wound-healing assay, Transwell assay, and flow cytometry were used to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…arrest in U87MG glioblastoma cells (Arcella et al, 2017). Cytotoxic triterpenoids from Antrodia camphorata (Li et al, 2020), polysaccharides from medicinal plants like Angelica sinensis (APs) (Zhand et al, 2017), Cyclocarya paliurus (CPP) (Du et al, 2020) and Aconitum coreanum (ACP1) (Sun et al, 2018) have also shown to induce apoptosis in U87MG and U251 glioblastoma cell lines. 106…”
Section: Flow Cytometry Analysis Of Etgipl1amentioning
confidence: 99%
“…arrest in U87MG glioblastoma cells (Arcella et al, 2017). Cytotoxic triterpenoids from Antrodia camphorata (Li et al, 2020), polysaccharides from medicinal plants like Angelica sinensis (APs) (Zhand et al, 2017), Cyclocarya paliurus (CPP) (Du et al, 2020) and Aconitum coreanum (ACP1) (Sun et al, 2018) have also shown to induce apoptosis in U87MG and U251 glioblastoma cell lines. 106…”
Section: Flow Cytometry Analysis Of Etgipl1amentioning
confidence: 99%